Forage Type and Maturity Effects on Yield and Nutritive Value - J. D. Holman; A. Obour; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2018)
Forage sorghum (Sorghum bicolorL.) and sorghum × sudan (Sorghum bicolor sssp. Drummondii) are important annual forages in the High Plains. Advancements in brown mid-rib (BMR) cultivars will likely affect forage yield and nutritive values. A study was initiated in 2017 at the Southwest Research-Extension Center near Garden City, KS, comparing one variety each of BMR and non-BMR forage sorghum and sorghum × sudan cultivars. Forage type and growth stage affected yield and nutritive value, and occasionally there was an interaction between forage type and maturity.
Keywords: Forage; sorghum; sudan; sorghum × sudan; maturity; quality; and nutritive value